Efektivitas Sistem Checks and Balances dalam Ketatanegaraan Indonesia - Ofinius Dawolo; Riki Al Farisi; Sugiono Eksantoso; Krisno Jatmiko (Lembaga Yasin AlSys, 2026)
Although the principle of separation of powers has received considerable attention in various constitutional studies, research specifically examining the practical effectiveness of checks and balances mechanisms following the amendments to the UUD NRI Tahun 1945 remains limited. This study aims to analyze the effectiveness of implementing the checks and balances system in Indonesia’s constitutional system and identify the factors influencing its implementation. The study employed a normative legal method with statutory and conceptual approaches. The legal materials analyzed included the UUD NRI Tahun 1945, laws and regulations, Constitutional Court decisions, books, and scholarly journal articles. The results indicate that, normatively, the checks and balances system has been designed through a relatively balanced distribution of authority among state institutions in accordance with the principle of separation of powers. However, its implementation continues to face various obstacles, including the dominance of political coalitions, the weak oversight function of the DPR, political interference in independent institutions, and a weak constitutional culture. These findings strengthen constitutional law scholarship on institutional accountability while broadening the understanding of the gap between normative design and the practice of power distribution within Indonesia’s presidential system. This study concludes that institutional independence and strengthened constitutional literacy are important factors in establishing an effective checks and balances mechanism. The implications of this study include a theoretical contribution to the development of constitutional law literature and practical implications for legislative reform and the strengthening of public constitutional education. This study also opens opportunities for further research on the empirical performance of state institutions in carrying out their functions of oversight and balancing power.